Association of TCF7L2 Polymorphism with Diabetic Nephropathy in the South Indian Population. (7th July 2015) - Bodhini, Dhanasekaran; Chidambaram, Manickam; Liju, Samuel; Prakash, Visvanathan G.; Gayathri, Vijay; Shanthirani, Coimbatore S.; Ranjith, Unnikrishnan; Anjana, Ranjit M.; Mohan, Viswanathan; Radha, Venkatesan
Summary The transcription factor 7‐like 2 (TCF7L2) gene plays a significant role in the development of type 2 diabetes and diabetic nephropathy. The aim of this study was to investigate the association of TCF7L2 rs12255372 (G/T)polymorphism with type 2 diabetic nephropathy in the South Indian population. A total of 2102 subjects, 927 normal glucose tolerant (NGT) subjects, 598 type 2 diabetic subjects without nephropathy (DM), and 577 type 2 diabetic subjects with nephropathy (DN) were genotyped by MassARRAY. As compared to the NGT group, the odds ratio (adjusted for age, sex, BMI, HbA1c, and systolic BP) computed for the GT/TT genotype taking the GG genotype as reference was found to be 2.02 (95% CI: 1.16‐3.51, p = 0.013) for DN and 1.94 (95% CI: 1.36‐2.78, p = 0.0002) for DM. The genotype frequency was not significantly different between the DM and DN groups. In conclusion, the rs12255372 polymorphism in the TCF7L2 gene is associated with type 2 diabetes and DN but its association with DN is mediated through diabetes.